Magnetoimpedância e dinâmica da magnetização em nanoestruturas ferromagneto/Cu (Ag)/ferromagneto - Corrêa, Marcio Assolin (2007)
In this work the static and dynamic magnetic properties are investigated in FM/i/Cu(Ag)/i/FM tri-layer structured samples where FM is the ferromagnetic multilayer and i is the SiO2 isolating layer. All samples have been deposited by magnetron sputtering on a glass substrate with a 50 Å Ta buffer layer. The models proposed by L. Spinu for the calculus of the transverse susceptibility and by L.V. Panina for the calculus of the magnetoimpedance in a tri-layer sample were considered in order to try to describe the MI effect for the produced samples. The connection of these models permits, just knowing the ferromagnetic free energy density, the simulation of the impedance for a tri-layer in a large frequency range. The real and imaginary parts of the impedance have been measured as a function of the frequency (100 kHz up to 1.8 GHz) and of the static magnetic field (±300 Oe). It was possible, varying the FM part in the tri-layer, using FeCuNbSiB/Cu, NiFe/Cu and NiFe/Ag, and parameters as width of the metallic layer (Wm) (Cu or Ag) to control the frequency value where the MI maximum occurs. Variations up to 220 % were measured for the sample with FM = FeCuNbSiB/Cu and Wm = 1,00 mm in 300 MHz. The connection of the models and an adequate energy configuration became possible to simulate the magnetoimpedance curves as a function of the magnetic field for frequencies up to 1.4 GHz. For frequencies higher than 1.4 GHz, effects of the distribution of the field induce the appearance of positive peaks for low fields and this effect can be associated to different resonance modes that generate discordance with respect to the simulation.